1997
DOI: 10.1042/bj3280353
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive internalization of cystic fibrosis transmembrane conductance regulator occurs via clathrin-dependent endocytosis and is regulated by protein phosphorylation

Abstract: Although the cystic fibrosis transmembrane conductance regulator (CFTR) is primarily implicated in the regulation of plasmamembrane chloride permeability, immunolocalization and functional studies indicate the presence of CFTR in the endosomal compartment. The mechanism of CFTR delivery from the cell surface to endosomes is not understood. To delineate the internalization pathway, both the rate and extent of CFTR accumulation in endosomes were monitored in stably transfected Chinese hamster ovary (CHO) cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
138
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 52 publications
6
138
0
Order By: Relevance
“…Considering that clathrin-coated pits constitute ϳ2% of the cell surface (18), our findings suggest that the double mutant has completely lost the ability to concentrate in these surface domains. This result has particular significance given the increasing evidence that CFTR enters the endocytic pathway via clathrin-coated pits (2,4,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that clathrin-coated pits constitute ϳ2% of the cell surface (18), our findings suggest that the double mutant has completely lost the ability to concentrate in these surface domains. This result has particular significance given the increasing evidence that CFTR enters the endocytic pathway via clathrin-coated pits (2,4,19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that CFTR is internalized from the cell surface (1-3) through clathrin-coated pits (2,4). Furthermore, CFTR has been shown to interact with PDZ-domain-containing proteins at its COOH terminus (5,6) and syntaxin 1A at its NH 2 terminus (7,8).…”
mentioning
confidence: 99%
“…Functionally active CFTR can be found in purified clathrin-coated vesicles derived from cultured cells and native tissues that constitutively express CFTR (11). Furthermore, studies examining CFTR internalization demonstrate that perturbation of clathrin-coated vesicle formation inhibits the removal of CFTR from the plasma membrane (12,13). More recently, we have shown that in polarized epithelial cells, CFTR is internalized solely through clathrin-coated vesicles and is excluded from other endocytic pathways such as caveolae (12), suggesting that CFTR is specifically recruited to the clathrin-coated vesicle pathway for endocytosis.…”
mentioning
confidence: 95%
“…Thus, immunologically detectable and functionally active CFTR is present in clathrin-coated vesicles isolated from both cultured epithelial cells and intact native tissue (11,29). Moreover, we and others have recently shown that inhibition of clathrin-mediated endocytosis causes a retention of CFTR at the cell surface (12,13). In contrast, disruption of alternate internalization pathways, such as caveolae, has no 1, 3, 5) or GST-CT (lanes 2, 4, 6) was incubated with adaptors isolated from bovine brain.…”
Section: Conformational Models Of the Tyrosine-based Motif In The Carmentioning
confidence: 99%
“…Compelling evidence indicates that CFTR enters endosomal compartments through the clathrinmediated endocytic pathway (9 -12). Furthermore, perturbation of clathrin-coated vesicle formation inhibits the removal of CFTR from the plasma membrane (12,13).…”
mentioning
confidence: 99%